The Diagnostic Value of Flow Cytometry in DOCK8 Deficiency - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; ÖĞÜLÜR, İSMAİL; BARIŞ, SAFA (TURKISH SOC IMMUNOLOGY, 2019)
Introduction: DOCK8 deficiency is a combined immunodeficiency with severe eczema, food allergy and autoimmunity. Early diagnosis is important for the treatment of patients. In this study, diagnostic value of flow cytometric detection of DOCK8 protein expression was evaluated in patients with DOCK8 deficiency. Material and Methods: Seven patients with DOCK8 deficiency and 20 healthy controls were enrolled in the study. Peripheral blood mononuclear cells (PBMCs) were isolated from patients and healthy controls, and DOCK8 protein expressions were detected. The data were analyzed as raw mean fluorescein intensity (MFI) and difference in MFI (Delta MFI) between cells stained in patients and healthy controls with and-DOCK8 antibody and isotype control. As the experiments were done on different days, the Delta MPI values obtained were normalized according to the current healthy control values and percent values were calculated. Results: The median age of DOCK8 patients was 12 years (8-15). Six of the patients have large deletions and 1 has a missense mutation in DOCK8 gene. Raw MFI values (p=0.0008) and normalized Delta MFI-percent values (p<0.0001) were significantly lower in DOCK8 patients compared to healthy controls. The patient with missense mutation had a raw MFI value close to the control (patient MFI: 23.70, control MFI: 35.50). Median of raw MFI was 4.95 (3.65-5.67) in patients and 26.2 (21.6-32.1) in healthy controls. Conclusion: Flow cytometric detection of DOCK8 protein is very important for the diagnosis of DOCK8 deficiency since the deletion mutations cause almost complete loss of DOCK8 protein expression, while patients with missense mutations could have nearly normal levels of protein, and this can lead to the underestimation of the diagnosis. Therefore, flow cytometric detection is an adjunct method for the diagnosis of DOCK8 disease, and genetic analysis should be offered to all suspicious cases.
Keywords: Flow cytometer; DOCK8; mean fluorescein intensity; deletion; missense mutation; CYTOKINESIS 8 DOCK8; DEDICATOR